2022
DOI: 10.1021/acs.jpcb.2c03078
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Optical Properties of Azobenzene Derivatives Modified with an (Amino)naphthalene Moiety

Abstract: The design of two-photon absorbing azobenzene (AB) derivatives has received much attention; however, the two-photon absorption (2PA) properties of bis-conjugated azobenzene systems are relatively less explored. Here, we present the synthesis of six azobenzene derivatives and three bis-azobenzenes substituted (or not) at para position(s) with one or two amino group(s). Their linear and nonlinear absorption properties are studied experimentally and theoretically. The switching behavior and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…The cross section of 2PA of RC 8 R is even higher than 2PA organometallic platinum end-capped octatetrayne measured at similar wavelengths . At the same time, 2PA of compound RC 8 R might be regarded as rather strong if some of the best diazobenzenes (entries 10–12) are considered. …”
Section: Dft Calculationsmentioning
confidence: 89%
“…The cross section of 2PA of RC 8 R is even higher than 2PA organometallic platinum end-capped octatetrayne measured at similar wavelengths . At the same time, 2PA of compound RC 8 R might be regarded as rather strong if some of the best diazobenzenes (entries 10–12) are considered. …”
Section: Dft Calculationsmentioning
confidence: 89%
“…Further, under the specialized circumstances, uptake of additional two electrons leads to the cleavage of the −N−N− bond to the imido form (Scheme 1). [8] Metallated azobenzene is also recently shown to extend modulation of the NLO (non‐linear optical) response with special reference to the free ligand [9] …”
Section: Introductionmentioning
confidence: 99%
“…[8] Metallated azobenzene is also recently shown to extend modulation of the NLO (non-linear optical) response with special reference to the free ligand. [9] On the other hand, environmentally hazardous waste produces out of the extensive usage of industrially significant azo dyes demands its facile degradation. Reduction of azocontaining compounds is thus considered as the first step forward in the direction of the degradation process.…”
Section: Introductionmentioning
confidence: 99%
“…13 Dudek et al elucidated the contribution of π-conjugation and substituent effects to the linear and nonlinear optical properties of mono- and bis-azobenzene compounds based on experimental and theoretical approaches. 14 For porphyrin molecules, Palummo et al theoretically investigated the electronic and optical properties of free base porphyrin and free base tetraphenyl porphyrin molecules (H 2 TPP) by using density functional theory and many-body perturbation theory. 4 Lopes et al demonstrated that endocyclic substituents can make asymmetric Q-bands of free base porphyrins relatively symmetric.…”
Section: Introductionmentioning
confidence: 99%